Pornography and women's sexual pleasure: Accounts from young women in Australia. (August 2019) - Ashton, Sarah; McDonald, Karalyn; Kirkman, Maggie
Understanding how young women experience pornography is a modern imperative in promoting sexual health. There has been, until now, no Australian research exploring what pornography means to women in relation to sexual pleasure. We conducted in-depth interviews with 27 women from around Australia. A thematic analysis of their accounts, supported by narrative theory, revealed that pornography both enhanced and interfered with pleasure. Women described pornography's contributions to the enhancement of pleasure through solo pleasure, shared viewing with partners, discovering new sexual preferences, and reassurance about body appearance. Pornography was constructed as interfering with pleasure through its misrepresentation (of bodies, sexual acts, and expression of pleasure), women's concern for actors' wellbeing, and its disruption of intimacy. Accounts were consistent with women's place in a culture that subordinates female pleasure to male pleasure. It was evident in women's accounts that pornography plays complex, dynamic roles in the production of pleasure, acting in the domains of physiology, psychology, relationships, ethics, society, and culture.